Hybrid composite membrane and preparation method thereof
By adding modified graphene oxide powder and modified hydrotalcite powder to the polyvinylidene fluoride nanofiltration membrane, and preparing hybrid composite membranes by in-situ polymerization, the problems of flux attenuation and short life of the polyvinylidene fluoride nanofiltration membrane are solved, and high-throughput and long-life membrane performance is achieved.
Patent Information
- Application Number
- CN202510386625.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-03-31
AI Technical Summary
The flux of polyvinylidene fluoride nanofiltration membrane has fast attenuation and short life, making it difficult to maintain stable penetration flux and selectivity in strong polar organic solvents for a long time.
Modified graphene oxide powder and modified hydrotalcite powder were used as inorganic nanoparticles to prepare hybrid composite films by in situ polymerization to increase the hydrophilicity and flux of the film, and improve the film's stain resistance through the addition of piperazine.
It significantly improves the water flux and service life of the hybrid composite film, slows down the flux attenuation, and is easy to obtain, the preparation process is simple, and is suitable for industrial production.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of membrane separation, and in particular relates to a hybrid composite membrane and a preparation method thereof. Background Art
[0002] Membrane technology has a very broad application prospect in the field of water treatment. It has the characteristics of low cost, small footprint, good treatment effect and little environmental pollution. It can effectively solve resource and environmental problems.
[0003] Solvent-resistant nanofiltration is based on nanofiltration, and the membrane materials are screened so that the prepared nanofiltration membrane can be used in high-temperature, highly polar solutions. However, the large-scale application of solvent-resistant nanofiltration is still rare. The main problem is that the flux of the current solvent-resistant nanofiltration membrane is still low, and it is difficult to maintain a stable permeation flux and selectivity in highly polar organic solvents for a long time. The development of solvent-resistant nanofiltration membranes with high flux and high solvent resistance is a research hotspot.
[0004] Polyvinylidene fluoride has high water separation efficiency, strong toughness, good chemical stability, heat resistance, and mechanical stability. It can be dissolved in certain highly polar organic solvents at relatively low temperatures and is easy to prepare membranes using the phase inversion method. However, the surface energy of polyvinylidene fluoride membranes is extremely low, and they are highly hydrophobic. They easily absorb grease and clog the membrane pores, resulting in low water flux after membrane formation. When separating sewage, they adsorb pollutants severely, the flux decays quickly, and the membrane life is short. Therefore, it is necessary to propose an improved method for increasing the flux and life of polyvinylidene fluoride.
[0005] The patent application document with publication number CN103657446A discloses a polyvinylidene fluoride hollow fiber membrane, which is prepared from polyvinylidene fluoride, sodium dodecyl sulfate, ethylene glycol monostearate, silicon dioxide, dimethyl sulfoxide, polyvinyl pyrrolidone, triethyl phosphate, calcium carbonate, sodium dodecylbenzene sulfonate, polyethylene glycol, dimethylacetamide, sodium dodecylaminopropionate, deionized water, polyvinyl alcohol, methylcellulose, dimethylformamide, hexadecyltrimethylammonium bromide, fatty amine polyoxyethylene ether, and polyoxyethylene. This polyvinylidene fluoride hollow fiber membrane has high compressive and tensile strength, high flux and flexibility, but it does not improve the technical problem of short life caused by polyvinylidene fluoride adsorbing pollutants.
[0006] The patent application document with publication number CN117563428A discloses a method for preparing a pressure-resistant high-flux polyvinylidene fluoride nanofiltration membrane, wherein a polyvinylidene fluoride composite nanofiltration membrane is prepared by phase inversion method, in-situ growth method and interfacial polymerization, the hydrophilicity of the polyvinylidene fluoride membrane is improved by adding hydrophilic inorganic nanoparticles, and a hydroxyl iron nanoparticle layer is prepared by in-situ growth on the surface of the blended membrane, thereby improving the stability and permeability of the nanofiltration separation layer obtained by subsequent interfacial polymerization. However, this polyvinylidene fluoride nanofiltration membrane does not improve the flux of the polyvinylidene fluoride nanofiltration membrane. Summary of the invention
[0007] In order to solve the technical problems existing in the related art such as fast flux attenuation and short life of polyvinylidene fluoride nanofiltration membrane, the purpose of the present invention is to provide a hybrid composite membrane and a preparation method thereof.
[0008] In order to achieve the above object, the technical solution of the present invention is as follows: A method for preparing a hybrid composite membrane comprises the following steps: S1: mixing polyvinylidene fluoride powder, nanoparticles and N,N-dimethylformamide, and performing ultrasonic dispersion to obtain a dispersion; S2: adding piperazine and polyethylene glycol to the dispersion obtained in step S1, stirring, heating, and then standing to degas, to obtain a casting solution; S3: pouring the casting solution obtained in step S2 onto a glass plate, scraping it into a film with a scraper, and then immersing it in a pure water coagulation bath for phase inversion to obtain a hybrid composite membrane; The nanoparticles are composed of modified graphene oxide powder and modified hydrotalcite powder in a mass ratio of 7-11:3-5.
[0009] In the present invention, modified graphene powder and modified hydrotalcite powder are used as inorganic particles and added to the hybrid composite membrane, so that the nano inorganic particles are uniformly hybridized into the polyvinylidene fluoride film layer, so that the prepared hybrid composite membrane has a higher water flux and improves the service life of the hybrid composite membrane. Piperazine is added to the casting liquid to increase the hydrophilicity of the hybrid composite membrane, so that the surface of the prepared hybrid composite membrane is rich in water-phase monomer piperazine, and the hybrid composite membrane is prepared by an in-situ polymerization method, which not only solves the problem of poor surface wettability of the polyvinylidene fluoride membrane, but also slows down the flux attenuation of the polyvinylidene fluoride membrane, and at the same time improves the stability of the hybrid composite membrane.
[0010] Furthermore, the preparation method of the modified graphene oxide powder is: mixing graphene oxide and deionized water evenly, then adding tartaric acid and bromoacetic acid, ultrasonicating, centrifuging, removing the lower precipitate, washing with deionized water until neutral, drying, and grinding to obtain modified graphene oxide powder.
[0011] Graphene oxide has a two-dimensional layered structure, and its structure is rich in oxygen-containing functional groups. It has excellent dispersibility, good chemical stability and high specific surface area in water or most polar solvents, and can effectively increase the flux of the hybrid composite membrane. However, it cannot solve the flux attenuation of the hybrid composite membrane. In the present invention, graphene oxide is modified in tartaric acid and bromoacetic acid, so that the number of oxygen-containing functional groups rich in graphene oxide is increased, thereby increasing the hydrophilic sites on the surface of the hybrid composite membrane, improving the anti-fouling ability of the hybrid membrane layer, effectively reducing the flux attenuation of the hybrid composite membrane, and increasing the life of the hybrid composite membrane.
[0012] Furthermore, in the preparation method of modified graphene, the mass ratio of graphene oxide to tartaric acid and bromoacetic acid is 1:13-15:6-9; the frequency of the ultrasound is 200-300kHz, the ultrasound time is 3.5-4h; and the drying temperature is 55-60°C.
[0013] Furthermore, the preparation method of the modified hydrotalcite powder is as follows: (1) placing bamboo powder in a tube furnace, heating, pyrolyzing, cooling and sieving, placing the powder after passing through a 400-mesh sieve into a mixed solution of a nitric acid solution and a sulfuric acid solution and soaking it, taking it out and washing it with deionized water until it is neutral, drying it, and grinding it to obtain carbon powder; (2) mixing the carbon powder, hydrotalcite powder, cobalt nitrate solution and nickel nitrate solution prepared in step (1), heating, stirring, adding ammonia water dropwise to adjust the pH value to 10-11, cooling, centrifuging, removing the lower layer of precipitate, vacuum drying it, and grinding it to obtain modified hydrotalcite powder.
[0014] Hydrotalcite has a layered structure, large specific surface area, and high reaction activity. Adding it to the hybrid composite membrane can increase the flux of the hybrid composite membrane, but it is easy to aggregate during the reaction process, reducing the active sites. Studies have found that the use of oxidized biochar to modify hydrotalcite can effectively improve the dispersion of hydrotalcite, obtain a larger interlayer spacing through the bound water between the metal hydroxide layers, and further improve the flux of the hybrid composite membrane.
[0015] Furthermore, in the preparation method of modified hydrotalcite powder, the heating temperature in step (1) is 800-900°C, the heating rate is 5-10°C / min, and the pyrolysis time is 4-4.5h; the volume ratio of the nitric acid solution and the sulfuric acid solution in the mixed solution of the nitric acid solution and the sulfuric acid solution is 1:1, the volume fraction of the nitric acid solution is 65%-70%, and the volume fraction of the sulfuric acid solution is 70%-75%; the soaking time is 1-2h, the drying temperature is 60-65°C, and the drying time is 24-28h; and the powder is ground to a particle size of 600-800nm.
[0016] Furthermore, in the preparation method of modified hydrotalcite powder, the mixing mass ratio of the carbon powder, hydrotalcite powder, cobalt nitrate solution and nickel nitrate solution in step (2) is 2-5:7-11:18-22:20-23, the concentration of the cobalt nitrate solution and the nickel nitrate solution is 0.5-0.7 mol / L; the heating temperature is 70-75°C, and the stirring time is 45-60 min; the mass fraction of the ammonia water is 25%-30%; the vacuum drying temperature is 80-85°C, and the vacuum drying time is 24-28 h.
[0017] Furthermore, in step S1 of the method for preparing the hybrid composite membrane, the mixing mass ratio of the polyvinylidene fluoride powder, the nanoparticles and the N,N-dimethylformamide is 8-12:3-6:19-23.
[0018] Furthermore, in the step S1 of the method for preparing the hybrid composite membrane, the ultrasonic frequency of the ultrasonic dispersion is 200-300 kHz, and the ultrasonic dispersion time is 4.5-5 h.
[0019] Furthermore, the mass fractions of the components in step S2 of the preparation method of the hybrid composite membrane are: 30-35 parts of dispersion liquid, 10-14 parts of piperazine, and 8-12 parts of polyethylene glycol; the polyethylene glycol is polyethylene glycol 1000.
[0020] Furthermore, in step S2 of the method for preparing the hybrid composite membrane, the stirring time is 3.5-4 hours, the heating temperature is 90-100° C., and the standing degassing time is 2.5-3 hours.
[0021] Furthermore, in step S3 of the method for preparing the hybrid composite membrane, the scraper thickness is 300 μm, the phase conversion time is 48-52 hours, and the pure water is replaced every 6 hours.
[0022] The present invention also provides a hybrid composite membrane prepared by using the method for preparing the hybrid composite membrane.
[0023] Compared with the prior art, the hybrid composite membrane and the preparation method thereof provided by the present invention have the following technical advantages: (1) The present invention adds modified graphene oxide powder and modified hydrotalcite powder to polyvinylidene fluoride, and prepares a hybrid composite membrane by an in-situ polymerization method, which has a high water flux; (2) In the present invention, by modifying graphene oxide and adding piperazine to the casting solution, the prepared hybrid composite membrane has good anti-fouling ability, can effectively slow down the flux attenuation caused by adsorption of pollutants, and has a long service life; (3) The raw materials of the hybrid composite membrane provided by the present invention are easily available and the preparation process is simple, which is conducive to industrial production. DETAILED DESCRIPTION
[0024] The technical scheme of the present invention is clearly and completely described below in conjunction with specific embodiments. The specific embodiments described are only partial embodiments of the present invention, rather than limitations of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work belong to the protection scope of the present invention.
[0025] Example 1 A method for preparing a hybrid composite membrane comprises the following steps: S1: polyvinylidene fluoride powder, nanoparticles and N,N-dimethylformamide are mixed in a mass ratio of 11:5:21, and ultrasonically dispersed at 280 kHz for 4.8 hours to obtain a dispersion; the nanoparticles are composed of modified graphene oxide powder and modified hydrotalcite powder in a mass ratio of 9:4; S2: Take 33 parts of the dispersion prepared in step S1, add 12 parts of piperazine and 10 parts of polyethylene glycol 1000, stir for 3.8 hours, heat to 95°C and stand for degassing for 2.8 hours to obtain a casting solution; S3: Set the scraper thickness to 300 μm, pour the casting solution obtained in step S2 onto a clean glass plate, and leave it in the air for 20 seconds, then immerse the glass plate in a pure water coagulation bath for 50 hours for phase inversion, and replace the pure water every 6 hours to obtain a hybrid composite membrane.
[0026] The preparation method of the modified graphene oxide powder is as follows: 1 part of graphene oxide is evenly mixed with 20 parts of deionized water, then 14 parts of tartaric acid and 8 parts of bromoacetic acid are added, ultrasonication is performed at 250 kHz for 3.8 hours, centrifugation is performed, the lower precipitate is removed, and the lower precipitate is washed with deionized water until it is neutral, dried at 58° C., and ground to a particle size of 750 nm to obtain the modified graphene oxide powder.
[0027] The preparation method of the modified hydrotalcite powder is as follows: (1) placing bamboo powder in a tube furnace, heating the temperature to 850°C at a rate of 8°C / min, pyrolyzing for 4.2 hours, cooling and sieving, placing the powder after passing through a 400-mesh sieve in a mixed solution of a nitric acid solution (volume fraction of 68%) and a sulfuric acid solution (volume fraction of 73%) in a volume ratio of 1:1, soaking for 1.5 hours, taking out and washing with deionized water until neutral, drying at 63°C for 26 hours, and grinding to obtain carbon powder; (2) The carbon powder, hydrotalcite, cobalt nitrate solution (0.6 mol / L) and nickel nitrate solution (0.6 mol / L) prepared in step (1) were mixed in a mass ratio of 4:9:20:21, heated to 73°C, stirred for 50 min, and ammonia water (mass fraction 28%) was added dropwise to adjust the pH value to 11. The mixture was cooled and centrifuged, and the lower precipitate was removed and vacuum dried at 83°C for 27 h, and ground to a particle size of 700 nm to obtain modified hydrotalcite.
[0028] Example 2 A method for preparing a hybrid composite membrane comprises the following steps: S1: polyvinylidene fluoride powder, nanoparticles and N,N-dimethylformamide are mixed in a mass ratio of 8:3:19, and ultrasonically dispersed at 200 kHz for 5 hours to obtain a dispersion; the nanoparticles are composed of modified graphene oxide powder and modified hydrotalcite powder in a mass ratio of 7:3; S2: Take 30 parts of the dispersion prepared in step S1, add 10 parts of piperazine and 8 parts of polyethylene glycol 1000, stir for 3.5 hours, heat to 90°C and stand for degassing for 3 hours to obtain a casting solution; S3: Set the scraper thickness to 300 μm, cast the casting solution obtained in step S2 onto a clean glass plate, and leave it in the air for 20 seconds, then immerse the glass plate in a pure water coagulation bath for 48 hours for phase inversion, and replace the pure water every 6 hours to obtain a hybrid composite membrane.
[0029] The preparation method of the modified graphene oxide powder is as follows: 1 part of graphene oxide is evenly mixed with 20 parts of deionized water, then 13 parts of tartaric acid and 6 parts of bromoacetic acid are added, ultrasonication is performed at 200 kHz for 4 hours, centrifugation is performed, the lower precipitate is removed, and the lower precipitate is washed with deionized water until it is neutral, dried at 55° C., and ground to a particle size of 700 nm to obtain the modified graphene oxide powder.
[0030] The preparation method of the modified hydrotalcite powder is as follows: (1) placing bamboo powder in a tube furnace, heating it to 800°C at a rate of 5°C / min, pyrolyzing it for 4.5 hours, cooling and sieving it, placing the powder after passing through a 400-mesh sieve in a mixed solution of a nitric acid solution (volume fraction of 65%) and a sulfuric acid solution (volume fraction of 70%) in a volume ratio of 1:1 for 1 hour, taking it out and washing it with deionized water until it is neutral, drying it at 60°C for 28 hours, and grinding it to obtain carbon powder; (2) mixing the carbon powder prepared in step (1), hydrotalcite powder, cobalt nitrate solution (0.5 mol / L) and nickel nitrate solution (0.7 mol / L) in a mass ratio of 2:7:18:20, heating it to 70°C, stirring it for 45 minutes, adding ammonia water (mass fraction of 25%) dropwise to adjust the pH value to 10, cooling it, centrifuging it, taking out the lower layer of precipitate, vacuum drying it at 80°C for 28 hours, grinding it to a particle size of 600 nm, and obtaining the modified hydrotalcite powder.
[0031] Example 3 A method for preparing a hybrid composite membrane comprises the following steps: S1: polyvinylidene fluoride powder, nanoparticles and N,N-dimethylformamide are mixed in a mass ratio of 12:6:23, and ultrasonically dispersed at 300 kHz for 4.5 hours to obtain a dispersion; the nanoparticles are composed of modified graphene oxide powder and modified hydrotalcite powder in a mass ratio of 11:5; S2: Take 35 parts of the dispersion prepared in step S1, add 14 parts of piperazine and 12 parts of polyethylene glycol 1000, stir for 4 hours, heat to 100° C. and stand for degassing for 2.5 hours to obtain a casting solution; S3: Set the scraper thickness to 300 μm, pour the casting solution obtained in step S2 onto a clean glass plate, and leave it in the air for 20 seconds, then immerse the glass plate in a pure water coagulation bath for 52 hours for phase inversion, and replace the pure water every 6 hours to obtain a hybrid composite membrane.
[0032] The preparation method of the modified graphene oxide powder is as follows: 1 part of graphene oxide is evenly mixed with 20 parts of deionized water, then 15 parts of tartaric acid and 9 parts of bromoacetic acid are added, ultrasonication is performed at 300kHz for 3.5 hours, centrifugation is performed, the lower precipitate is removed, and the lower precipitate is washed with deionized water until it is neutral, dried at 60°C, and ground to a particle size of 800nm to obtain the modified graphene oxide powder.
[0033] The preparation method of the modified hydrotalcite powder is as follows: (1) placing bamboo powder in a tube furnace, heating it to 900° C. at a rate of 10° C. / min, pyrolyzing it for 4 hours, cooling and sieving it, placing the powder after passing through a 400-mesh sieve in a mixed solution of a nitric acid solution (volume fraction of 70%) and a sulfuric acid solution (volume fraction of 75%) in a volume ratio of 1:1 for immersion for 2 hours, taking it out and washing it with deionized water until it is neutral, drying it at 65° C. for 24 hours, and grinding it to obtain carbon powder; (2) mixing the carbon powder prepared in step (1), hydrotalcite powder, cobalt nitrate solution (0.7 mol / L) and nickel nitrate solution (0.5 mol / L) in a mass ratio of 5:11:22:23, heating it to 75° C., stirring it for 60 minutes, adding ammonia water (mass fraction of 30%) dropwise to adjust the pH value to 11, cooling it, centrifuging it, taking out the lower layer of precipitate, vacuum drying it at 85° C. for 24 hours, grinding it to a particle size of 800 nm, and obtaining the modified hydrotalcite powder.
[0034] Comparative Example 1 The preparation method of the hybrid composite membrane described in this comparative example is similar to that of Example 1. The difference between this comparative example and Example 1 is that the nanoparticles described in this comparative example are all modified graphene oxide powder.
[0035] Comparative Example 2 The preparation method of the hybrid composite membrane in this comparative example is similar to that in Example 1. The difference between this comparative example and Example 1 is that the nanoparticles in this comparative example are all modified hydrotalcite powder.
[0036] Comparative Example 3 The preparation method of the hybrid composite membrane in this comparative example is similar to that in Example 1. The difference between this comparative example and Example 1 is that an equal amount of deionized water is used instead of piperazine in step S2 of the preparation method of the hybrid composite membrane in this comparative example.
[0037] Comparative Example 4 The preparation method of the hybrid composite membrane described in this comparative example is similar to that of Example 1. The difference between this comparative example and Example 1 is that the nanoparticles described in this comparative example are composed of modified graphene oxide powder and modified hydrotalcite powder in a mass ratio of 4:9.
[0038] Comparative Example 5 The preparation method of the hybrid composite membrane in this comparative example is similar to that in Example 1. The difference between this comparative example and Example 1 is that an equal amount of bromoacetic acid is used instead of tartaric acid in the preparation method of the modified graphene oxide in this comparative example.
[0039] Comparative Example 6 The preparation method of the hybrid composite membrane in this comparative example is similar to that in Example 1. The difference between this comparative example and Example 1 is that an equal amount of hydrotalcite is used instead of modified hydrotalcite in this comparative example.
[0040] Test example Film surface wettability test: The water contact angles (WCAs) of the films prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were measured using a semiconductor contact angle surface tension meter by a static hanging drop method.
[0041] Flux test: Use an effective filtration area of 10.18 cm 2 The dead-end filtration device tests the flux of the hybrid composite membranes obtained in Example 1 to Example 3 and Comparative Example 1 to Comparative Example 6, specifically: (1) Pure water flux test: Under an operating pressure of 0.15 MPa, pure water was pressurized to pass through the hybrid composite membrane for 30 min until the system was stable. Then the operating pressure was switched to 0.10 MPa and filtration was continued for 2 h. Pure water was collected every 10 min and its volume was recorded. The pure water flux was calculated as follows: J0 = V / St, where V is the volume of pure water passing through the membrane, S is the effective area for water to pass through, and t is the time for each water extraction.
[0042] (2) Oil solution flux test: The test process of oil solution flux is similar to that of pure water flux (using membrane to filter 400 mg / L n-hexadecane emulsion). The oil content of the aqueous solution before and after membrane filtration is tested by a total organic carbon analyzer (Shimadzu TOC-L CPH, Japan), and the reversible fouling degree (RFR) and relative flux decay rate (RFD) of the hybrid composite membrane are calculated and evaluated. The calculation formulas for RFR and RFD are: RFR=J w / J0×100%,RFD=(J0-J c ) / J0×100%, where J w is the pure water recovery flux measured after membrane flushing, J c is the permeate flux after running in the feed solution for 120 min, and J0 is the pure water flux.
[0043] Test results: The test results are shown in Table 1.
[0044] Table 1 Test results of hybrid composite membranes
[0045] As shown in Table 1, the water contact angle of the hybrid composite membranes prepared in Examples 1 to 3 of the present invention is 38.9-45.1°, which indicates that the hybrid composite membranes have good wetting properties; the pure water flux is 1152.78-1215.93 L / (m 2 h), the reversible contamination degree is 84.21%-87.64%, and the relative flux attenuation rate is 20.10%-23.24%, which shows that the hybrid composite membrane has good flux and low flux attenuation, and has a long service life. Among them, the hybrid composite membrane prepared in Example 1 has the best wettability and flux, and is the best embodiment of the present invention.
[0046] Compared with Example 1, the nanoparticles described in Comparative Example 1 are all modified graphene oxide powder, but the water contact angle and pure water flux of the obtained hybrid composite membrane are reduced, which shows that the modified graphene oxide powder can improve the hydrophilicity of the hybrid composite membrane, and the modified graphene oxide and modified hydrotalcite powder can play a synergistic role as inorganic nanoparticles, effectively improving the pure water flux of the hybrid composite membrane; the nanoparticles described in Comparative Example 2 are all modified hydrotalcite powder, but the water contact angle of the obtained hybrid composite membrane increases, the pure water flux and the reversible pollution degree decrease, and the relative flux attenuation rate increases, which shows that the addition of modified graphene oxide powder can improve the hydrophilicity of the hybrid composite membrane, reduce the flux attenuation, and can work together with the modified hydrotalcite powder to improve the pure water flux of the hybrid composite membrane; in Comparative Example 3, an equal amount of deionized water is used instead of piperazine, but the water contact angle and relative flux attenuation rate of the obtained hybrid composite membrane are significantly increased, which shows that the addition of piperazine can solve the surface lubrication of the polyvinylidene fluoride membrane. The problem of poor wettability is solved, and the flux attenuation of the hybrid composite membrane is slowed down; in Comparative Example 4, the mass ratio of modified graphene oxide powder and modified hydrotalcite powder is changed, but the wettability and flux of the obtained hybrid composite membrane are affected to varying degrees, which shows that the mass ratio of modified graphene oxide powder and modified hydrotalcite powder in the present invention has been optimized; in Comparative Example 5, an equal amount of bromoacetic acid is used instead of tartaric acid, but the relative flux attenuation rate of the obtained hybrid composite membrane is increased, which shows that in the preparation process of modified graphene oxide, tartaric acid and bromoacetic acid work together to effectively increase the active sites on the surface of graphene oxide, thereby improving the anti-fouling ability of the hybrid composite membrane; in Comparative Example 6, an equal amount of hydrotalcite powder is used instead of modified hydrotalcite powder, but the flux and reversible pollution degree of the obtained hybrid composite membrane are significantly reduced, and the relative flux attenuation rate is increased, which shows that the use of oxidized biochar to modify hydrotalcite powder in the present invention can effectively improve the dispersibility of hydrotalcite powder, obtain a larger interlayer spacing, and improve the flux of the hybrid composite membrane.
[0047] The above embodiments are only preferred embodiments of the present invention, and are not intended to limit the present invention. Any person skilled in the art shall not modify the above embodiments without violating the spirit and scope of the present invention. Therefore, any modification, equivalent substitution and improvement made by those skilled in the art under the technical concept of the present invention shall still be covered by the claims of the present invention.
Claims
1. A method for preparing a hybrid composite membrane, characterized in that: The following steps are involved: S1: mixing polyvinylidene fluoride powder, nanoparticles and N,N-dimethylformamide, and performing ultrasonic dispersion to obtain a dispersion; S2: adding piperazine and polyethylene glycol to the dispersion obtained in step S1, stirring, heating, and then standing to degas, to obtain a casting solution; S3: pouring the casting solution obtained in step S2 onto a glass plate, scraping it into a film with a scraper, and then immersing it in a pure water coagulation bath for phase inversion to obtain a hybrid composite membrane; The nanoparticles are composed of modified graphene oxide powder and modified hydrotalcite powder in a mass ratio of 7-11:3-5.
2. The method for preparing a hybrid composite membrane according to claim 1, characterized in that: The preparation method of the modified graphene oxide powder is as follows: graphene oxide and deionized water are mixed evenly, then tartaric acid and bromoacetic acid are added, ultrasonication is performed, centrifugation is performed, a lower precipitate is taken out, the lower precipitate is washed with deionized water until it is neutral, drying is performed, and grinding is performed to obtain the modified graphene oxide powder.
3. The method for preparing a hybrid composite membrane according to claim 2, characterized in that: The mass ratio of graphene oxide to tartaric acid and bromoacetic acid is 1:13-15:6-9; the frequency of ultrasound is 200-300kHz, and the time of ultrasound is 3.5-4h; and the temperature of drying is 55-60°C.
4. The method for preparing a hybrid composite membrane according to claim 1, characterized in that: The preparation method of the modified hydrotalcite powder comprises the following steps: (1) placing bamboo powder in a tube furnace, heating, pyrolyzing, cooling and sieving, placing the powder after passing through a 400-mesh sieve into a mixed solution of a nitric acid solution and a sulfuric acid solution, soaking the powder, taking it out, washing it with deionized water until it is neutral, drying, grinding, and obtaining carbon powder; and (2) mixing the carbon powder, hydrotalcite powder, cobalt nitrate solution, and nickel nitrate solution obtained in step (1), heating, stirring, adding ammonia water dropwise to adjust the pH value to 10-11, cooling, centrifuging, removing the lower precipitate, vacuum drying, and grinding to obtain the modified hydrotalcite powder.
5. The method for preparing a hybrid composite membrane according to claim 4, characterized in that: The heating temperature in step (1) is 800-900° C., the heating rate is 5-10° C. / min, and the pyrolysis time is 4-4.5 h. The volume ratio of the nitric acid solution to the sulfuric acid solution in the mixed solution of the nitric acid solution and the sulfuric acid solution is 1:1, the volume fraction of the nitric acid solution is 65%-70%, and the volume fraction of the sulfuric acid solution is 70%-75%. The soaking time is 1-2 h, the drying temperature is 60-65° C., and the drying time is 24-28 h. The powder is ground to a particle size of 600-800 nm.
6. The method for preparing a hybrid composite membrane according to claim 4, characterized in that: The mixing mass ratio of the carbon powder, hydrotalcite powder, cobalt nitrate solution and nickel nitrate solution in step (2) is 2-5:7-11:18-22:20-23, the concentration of the cobalt nitrate solution and the nickel nitrate solution is 0.5-0.7 mol / L; the heating temperature is 70-75°C, and the stirring time is 45-60 min; the mass fraction of the ammonia water is 25%-30%; the vacuum drying temperature is 80-85°C, and the vacuum drying time is 24-28 h.
7. The method for preparing a hybrid composite membrane according to claim 1, characterized in that: In step S1, the mixing mass ratio of the polyvinylidene fluoride powder, nanoparticles and N,N-dimethylformamide is 8-12:3-6:19-23; the ultrasonic frequency of ultrasonic dispersion is 200-300kHz, and the ultrasonic dispersion time is 4.5-5h.
8. The method for preparing a hybrid composite membrane according to claim 1, characterized in that: The mass fractions of the components in step S2 are: 30-35 parts of dispersion, 10-14 parts of piperazine, and 8-12 parts of polyethylene glycol; the polyethylene glycol is polyethylene glycol 1000; the stirring time is 3.5-4 hours, the heating temperature is 90-100° C., and the standing degassing time is 2.5-3 hours.
9. The method for preparing a hybrid composite membrane according to claim 1, characterized in that: The thickness of the scraper in step S3 is 300 μm, the phase inversion time is 48-52 hours, and the pure water is replaced every 6 hours.
10. A hybrid composite membrane prepared according to the method for preparing a hybrid composite membrane according to any one of claims 1 to 9.
Citation Information
Patent Citations
Polyvinylidene fluoride hollow-fiber membrane
CN103657446A
Preparation method of pressure-resistant high-flux polyvinylidene fluoride nanofiltration membrane
CN117563428A
High-performance lyophilic PVDF / GO-lysine composite membrane
CN105413494A
Chitosan functionalized graphene oxide / polyvinylidene fluoride hybrid ultrafiltration membrane and preparation method thereof
CN105903359A
Preparation method of high-flux fouling resistant nanofiltration membrane
CN108744994A